Molecular Cloning and Expression of Haloacid Dehalogenase Gene from a Local Pseudomonas aeruginosa ITB1 Strain and Tertiary Structure Prediction of the Produced Enzyme - Enny Ratnaningsih; Lousiana Dwinta Utami; Nurlaida Nurlaida; Rindia Maharani Putri (Jurnal Kimia Sains dan Aplikasi, 2021)
Organohalogens are widely utilized as pesticides, herbicides, solvents, and for many other industrial purposes. However, the use of these compounds caused some negative impacts to the environment due to their toxicity and persistency. In the light of this, some microbes have been identified and employed to perform dehalogenation, converting halogenated organic compounds to non-toxic materials. In this research, we successfully cloned and sequenced the haloacid dehalogenase gene from a local Pseudomonas aeruginosa ITB1 strain, which is involved in the degradation of monochloroacetate. First, the haloacid dehalogenase gene was amplified by PCR using a pair of primers designed from the same gene sequences of other P. aeruginosa strains available in the GenBank. The cloned gene in pGEM-T in E. coli TOP10 was sequenced, analyzed, and then sub-cloned into pET-30a(+) for expression in E. coli BL21 (DE3). To facilitate direct sub-cloning, restriction sequences of EcoRI (G/AATTC) and HindIII (A/AGCTT) were added to the forward and reversed primers, respectively. The expressed protein in E. coli BL21 (DE3) appeared as a 26-kDa protein in SDS-PAGE analysis, which is in good agreement with the size predicted by ExPASy Protparam. We obtained that the best expression in LB liquid medium was achieved with 0.01 mM IPTG induction at 30°C incubation for 3 hours. We also found that the enzyme is more concentrated in the pellet cells as inclusion bodies. Furthermore, the in-silico analysis revealed that this enzyme consists of 233 amino acid residues. This enzyme’s predicted tertiary structure shows six β-sheets flanked by α-helixes and thus belongs to Group II haloacid dehalogenase. Based on the structural prediction, amino acid residues of Asp7, Ser121, and Asn122 are present in the active site and might play essential roles in catalysis. The presented study laid the foundation for recombinant haloacid dehalogenase production from P. aeruginosa local strains. It provided an insight into the utilization of recombinant local strains to remediate environmental problems caused by organohalogens.